Impediments to the Schumpeterian Process in the Replacement of Large Firms - FACCIO, MARA; MCCONNELL, JOHN J. (Journal of Finance, 2025)
ABSTRACT We use newly assembled data overall encompassing up to 75 countries and starting circa 1910, to study impediments to the Schumpeterian process of creative destruction as it “proceeds by competitively destroying old businesses.” Political connections appear to represent an obstacle to the destructive part of the Schumpeterian process in the replacement of large firms. When accompanied by regulations that restrict entry, political connections can play a role in allowing large firms to remain large. When connected to Fogel, Morck, and Yeung (2008, Journal of Financial Economics 89, 83–108), the results imply that political connections, combined with barriers to entry, can retard economic development.